2020
DOI: 10.1007/s43452-020-00081-7
|View full text |Cite
|
Sign up to set email alerts
|

Seismic behavior of frost-damaged squat RC shear walls under artificial climate environment: a further experimental research

Abstract: In cold environment, the damage of freezing and thawing poses a great threat to the safety of concrete structures. In this study, six frost-damaged squat reinforced concrete (RC) shear walls were subjected to low cyclic reversal loading to investigate the effects of axial compression ratio, concrete strength and freeze-thaw cycles (FTCs) on the seismic performance of squat RC shear walls. The seismic behavior of the test specimens was evaluated in terms of the frost action at the microstructure level, frost-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…(3) When the pier top load exceeds the peak load P m , the RC pier is in the degradation stage, and the pier top load and unloading stiffness gradually decrease. The loading path is loaded according to 8-16 (12)(13)(14)(15)(16)(17)(18)(19). The loading path is loaded according to the degradation stiffness K 3 and calculated according to Equation (26).…”
Section: Determination Of Unloading Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) When the pier top load exceeds the peak load P m , the RC pier is in the degradation stage, and the pier top load and unloading stiffness gradually decrease. The loading path is loaded according to 8-16 (12)(13)(14)(15)(16)(17)(18)(19). The loading path is loaded according to the degradation stiffness K 3 and calculated according to Equation (26).…”
Section: Determination Of Unloading Stiffnessmentioning
confidence: 99%
“…The proposed restoring force model was suitable for the study of the seismic problem of RC piers in a freshwater environment. Zheng et al [15][16][17] established the restoring force model of (low shear span ratio) shear walls after freshwater freeze-thaw cycles, and the numerical analysis was carried out according to the relevant experiments. The effectiveness of the proposed model was verified by comparing the results of hysteresis curves and cumulative energy consumption between the experiment and numerical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the numerical simulation method was verified by comparing it with the experimental results. Zhang et al [18][19][20] conducted a numerical simulation of the shear wall and RC columns after freshwater freeze-thaw cycles using the fiber beam element method. Based on the pull-out test of reinforced concrete specimens, the degradation law of bond strength was established, which could consider the distribution of freeze-thaw damage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be concluded that the Bouc-Wen model, because of its limited number of parameters, provides the specific shape of the hysteresis loop given in Figure 1. However, the range of hysteresis loops observed in materials is much more diverse than the one provided by the Bouc-Wen model, since this range includes asymmetry of the loop, 13 pinching, 14,15 degrading, 16 or multiple loops. 17 This is why various authors proposed modifications of the Bouc-Wen model by incorporating more terms and parameters into the differential equation; see the survey paper.…”
Section: Introduction and Problem Statementmentioning
confidence: 99%